A New Design Security Issues Addressing and Challenges in Mobile Cloud Computing - Nirmal Kumar Gupta; Gaurav Raj (Mulia International Journal in Science and Technical, 2018)
The emergence of cloud computing has brought tremendous impact on software organiza-tions and software architecture design. With the development of cloud computing and mo-bile internet, mobile cloud computing is becoming a new mode of application. With the widespread development of mobile applications and advances in mobile cloud computing, some other forms of requirements and security issues have been emerged. Mobile cloud computing provides resources residing over cloud and services provided for mobile devices. These resources and services from cloud are available for mobile user over their mobile de-vices. It also provides benefits for developing specialized mobile applications for them. However, increased security and privacy risks exists due to data outsourcing and synchro-nization over the Internet. This research paper provides the review on mobile cloud compu-ting, its security issues, challenges and suggests some solutions.